Quality Indicators of Transanal Total Mesorectal Excision (TaTME) for Rectal Cancer - Martínez,María Labalde (2021)
Abstract Introduction Transanal total mesorectal excision (TaTME) has revolutionized the surgical techniques for lower-third rectal cancer. The aim of the present study was to analyze the outcomes of quality indicators of TaTME for rectal cancer compared with laparoscopic TME (LaTME). Methods A cohort prospective study with 50 (14 female and 36male) patients, with a mean age of 67 (range: 55.75 to 75.25) years, who underwent surgery for rectal cancer. In total, 20 patients underwent TaTME, and 30, LaTME. Every TaTME procedure was performed by experienced colorectal surgeons. The sample was divided into two groups (TaTME and LaTME), and the quality indicators of the surgery for rectal cancer were analyzed. Results There were no statistically significant differences regarding the patients and the main characteristics of the tumor (age, gender, American Society of Anesthesiologists [ASA] score, body mass index [BMI], tumoral stage, neoadjuvant therapy, and distance from the tumor to the external anal margin) between the two groups. The rates of: postoperativemorbidity (TaTME: 35%; LaTME: 30%; p=0.763);mortality (0%); anastomotic leak (TaTME: 10%; LaTME: 13%; p=0.722); wound infection (TaTME: 0%; LaTME: 3.3%; p=0.409); reoperation (TaTME: 5%; LaTME: 6.6%; p=0.808); and readmission (TaTME: 5%; LaTME: 0%; p=0.400), as well as the length of the hospital stay (TaTME: 13.5 days; LaTME: 11 days; p=0.538), were similar in both groups. There were no statistically significant differences in the rates of positive circumferential resection margin (TaTME: 5%; LaTME: 3.3%; p=0.989) and positive distal resection margin (TaTME: 0%; LaTME: 3.3%; p=0.400), the completeness of the TME (TaTME: 100%; LaTME: 100%), and the number of lymph nodes harvested (TaTME: 15; LaTME: 15.5; p=0.882) between two groups. Conclusion Transanal total mesorectal excision is a safe and feasible surgical procedure for middle/lower-third rectal cancer.